In Vivo Pharmacokinetics and Pharmacodynamics of the Lantibiotic NAI-107 in a Neutropenic Murine Thigh Infection Model - Lepak, Alexander J. (American Society for Microbiology, 2015)

(untitled) (Antimicrob Agents Chemother)
NAI-107 is a novel lantibiotic compound with potent in vitro activity against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). The purpose of this study was to examine the activity of NAI-107 against S. aureus strains, including MRSA, in the neutropenic murine thigh infection model. Serum pharmacokinetics were determined and time-kill studies were performed following administration of single subcutaneous doses of 5, 20, and 80 mg/kg body weight. The dose fractionation included total doses ranging from 1.56 to 400 mg/kg/72 h, divided into 1, 2, 3, or 6 doses. Studies of treatment effects against 9 S. aureus strains (4 methicillin-susceptible Staphylococcus aureus [MSSA] and 5 MRSA) using a 12-h dosing interval and total dose range of 1.56 to 400 mg/kg/72 h were also performed. A maximum effect (E(max)) model was used to determine the pharmacokinetic/pharmacodynamic (PK/PD) index that best described the dose-response data and to estimate the doses required to achieve a net bacteriostatic dose (SD) and a 1-log reduction in CFU/thigh. The pharmacokinetic studies demonstrated an area under the concentration-time curve (AUC) range of 26.8 to 276 mg · h/liter and half-lives of 4.2 to 8.2 h. MICs ranged from 0.125 to 0.5 μg/ml. The 2 highest single doses produced more than a 2-log kill and prolonged postantibiotic effects (PAEs) ranging from 36 to >72 h. The dose fractionation-response curves were similar, and the AUC/MIC ratio was the most predictive PD index (AUC/MIC, coefficient of determination [R(2)] = 0.89; maximum concentration of drug in serum [C(max)]/MIC, R(2) = 0.79; time [T] > MIC, R(2) = 0.63). A ≥2-log kill was observed against all 9 S. aureus strains. The total drug 24-h AUC/MIC values associated with stasis and a 1-log kill for the 9 S. aureus strains were 371 ± 130 and 510 ± 227, respectively. NAI-107 demonstrated concentration-dependent killing and prolonged PAEs. The AUC/MIC ratio was the predictive PD index. Extensive killing was observed for S. aureus organisms, independent of the MRSA status. The AUC/MIC target should be useful for the design of clinical dosing regimens.